ŉ Metodologie vir die beskrywing van konstruksionaliseringsnetwerke: Konstruksies met [in] as gevallestudie - van Huyssteen, Gerhard; Breed, Adri; Lande, Botha; Butler, Anneke; `Partridge, Maristi; Pilon, Suléne (Stellenbosch Papers in Linguistics Plus, 2023)
Views on constructionalisation and constructional change are at the forefront of construction grammar approaches to language change. In order to be able to talk about constructionalisation and constructional changes in a particular part of the constructicon, it is necessary to have both a diachronic and synchronic view of that network of constructions. The overall purpose of this contribution is to propose a methodology (i.e. a set of methods, principles, rules, etc. for a specific purpose within a specific theory / discipline) for the description and explanation of constructionalisation networks, i.e. networks with a temporal dimension that indicate the development of constructions. To illustrate this framework, we look at the constructionalisation network of "in" as a prepositional lexical item, as based on data from dictionaries and corpora. It is shown that changes in a construction network are (among other things) characterised by the presence of taboo constructions in that part of the network, and that constructions with taboo words can be taken as one of the starting points to search for constructional change and constructionalisations in a network._____________________________________________________________________________________Beskouings oor konstruksionalisering en konstruksieverandering is aan die voorpunt van konstruksiegrammatikabenaderings tot taalverandering. Ten einde oor konstruksionalisering en konstruksieveranderings in ŉ bepaalde deel van die konstruktikon te kan praat, is dit nodig dat ŉ mens ŉ diachroniese én sinchroniese blik op daardie netwerk van konstruksies moet hê. Die oorhoofse doel van hierdie bydrae is om ŉ metodologie (d.i. ŉ stel metodes, beginsels, reëls, ens. vir ŉ bepaalde doel binne ŉ bepaalde teorie/dissipline) voor te stel vir die beskrywing en verklaring van konstruksionaliseringsnetwerke, d.i. netwerke met ŉ tyddimensie waarmee die ontwikkeling van konstruksies aangedui word. Om hierdie raamwerk te illustreer, kyk ons na die konstruksionaliseringsnetwerk van in as preposisionele leksikale item, soos gebaseer op data uit woordeboeke en korpora. Daar word aangetoon dat veranderinge in ŉ konstruksienetwerk word (onder andere) gekenmerk deur die teenwoordigheid van taboekonstruksies in daardie deel van die netwerk en dat konstruksies met taboewoorde in as een van die vertrekpunte geneem kan word om soektogte na konstruksieverandering en konstruksionaliserings in ŉ netwerk te begin.